Tribological behaviors of natural attapulgite nanofibers as an additive for mineral oil investigated by orthogonal test method. (January 2021) - Yu, H.L.; Wang, H.M.; Yin, Y.L.; Song, Z.Y.; Zhou, X.Y.; Ji, X.C.; Wei, M.; Shi, P.J.; Bai, Z.M.; Zhang, W.
Abstract: Natural attapulgite nanofibers were added into lubricating oil to improve the tribological behaviors. Orthogonal experiment design was performed to study the effects of load, frequency, duration and concentration on the tribological properties of the additive by SRV reciprocating wear tester. Results indicate that the order that affects the tribological performances of the additive is load, concentration, frequency and duration. A tribolayer consisting of oxides, ceramics, silicates and graphite has generated on the rubbing surface lubricated by the attapulgite oil. Such layer with good lubricity, high hardness and hardness/elastic modulus ratio is conducive to the excellent tribological behaviors of the attapulgite. The formation is considered to be related to the special physico-chemical properties of attapulgite and tribological test conditions. Highlights: Tribological behavior of attapulgite as additive was studied by orthogonal tests. Order of tribological factors that affects the properties of attapulgite was obtained. Formation of the tribofilm was in situ monitored by ECR measurement during test. Nano mechanical properties of the tribofilm were studied by nanoindentation. Antiwear and lubricating mechanisms of attapulgite mineral was further clarified.